Determinants of Antiviral Treatment Initiation in a Hepatitis C-infected Population Benefiting from Universal Health Care Coverage - Romain Moirand; Marc Bilodeau; Suzanne Brissette; Julie Bruneau (Canadian Journal of Gastroenterology)
BACKGROUND AND AIMS: In view of increasing therapeutic efficacy, the delivery of hepatitis C virus (HCV) antiviral treatment is expected to increase. Yet practical experience reveals a low rate of treatment, particularly among intravenous drug users. The aim of the present study was to examine the prevalence of HCV treatment and identify factors associated with HCV treatment in a population of patients evaluated in an academic hepatology outpatient clinic between 2001 and 2002.